Biological Rhythm Disturbances in Drug-Free Adult ADHD Patients - Tarakçıoğlu, Mahmut Cem; Sakarya, Direnç; AKSOY, SENNUR GÜNAY; Sakarya, Ayşegül; Aksoy, Umut Mert (Psikofarmakoloji Derneği adına Mesut Çetin, 2019)
Objective: The aim of study was to examine the biological rhythms in drug-free ADHD patients with healthy controls in across-sectional study.Methods: 50 adult ADHD patients %26 female) between 17 and 42 years old (M=27.76 SD:6.80) and healthy controls (%56.6female) between 18 and 63 years old (M=31.39 SD:8.12) were recruited from Health Sciences University’s Bakirkoy MentalHealth Training and Research Hospital. Participants were assessed with clinical interview, Wender-Utah Adult ADHD RatingScale and the Biological Rhythms Interview of Assessment in Neuropsychiatry (BRIAN).Results: Adult ADHD patients scored higher on total scores (t=8.75, p<0.001), eating patterns (t=2.55, p<0.001), sleep patternssocial rhythm (t=3.41, p=0.001) and activity levels (t=3.0, p<0.001) in regarding to biologic rhythms. In the BRIAN subdomains;activity levels (t=4.59, p<0.001) and sleep-eating patterns (t=3.62, p<0.001) were also significantly different between the two groups.Conclusions: Our findings suggested that there was a significant difference between ADHD patients and healthy controls inmost dimensions of biorhythm.
Keywords: ADHD; Adult; Biorhythm; Chronotype